On the identity of the centipede Sogona cyclareata Attems, 1947 (Geophilomorpha, Geophilidae) - Fonseca, Régia Mayane Pacheco; Akkari, Nesrine; Chagas-Jr, Amazonas (Zootaxa, 2020)
The type material of Sogona cyclareata Attems, 1947 is revised. The syntype shares characters with representatives of the family Schendylidae and not the Geophilidae to which it is currently assigned. The species has the claw of the second maxillae pectinate and the labrum not divided into median and lateral portions. Sogona cyclareata presents also characters of the genus Schendylops Cook, 1899 such as the presence of two pores in each coxopleuron, ultimate legs without claws, and the arrangement of the sternal pores-fields. No Schendylops species known to date has the characters of S. cyclareata, so we propose the new combination Schendylops cyclareatus.